The Effect of Debt on Business Profit (Case Study at PT. Gudang Garam Tbk Listed on the Indonesia Stock Exchange for the 2015-2020 Period) - Dody Faraitody Teguh; Astri Dwi Andriani; Fitri Pebryanti (International Journal of Economics, Business Management and Accounting (IJEBMA), 2022)
Research conducted by the author to determine the effect of debt on operating profits at PT. Gudang Garam Tbk. Listed on the Indonesian Stock Exchange for the 2015-2020 period. The independent variable is debt, the dependent variable is operating profit. The sampling type chosen was purposive sampling. Quantitative data type. Secondary data sources include financial reports accessing www.idx.co.id and each company's website. The research results show that the effect of debt on business profits is two linear factors, characterized by the regression equation Ý = -1.242 + 0.519 x. This means that every time debt is increased by 1%, it will be followed by an increase in operating profit of 0.519 at a constant of 1.242. There is a very strong and significant influence between debt and business profits as shown by the Pearson product moment correlation coefficient r = 0.713 with tcount = 2.032, this value is greater than ttable = 2.132. In accordance with the correlation coefficient value above, the coefficient of determination is 0.508, which means that the influence of debt on business profits is 50.8% and the remaining 49.2% is explained by other variables not included in this analysis